Why are new sources of cosmic rays nearby the solar system needed?. Issue 9 (1st November 2022) - Stozhkov, Y.I.
Highlights: In the Galaxy active dwarf stars are the sources of cosmic rays. These particles are produced in stellar flares. The power of these stellar flares is enough to provide the density of energy of galactic cosmic rays observed in Galaxy. In stellar flares positrons are also produced. This production explains the positron excess recorded in space experiments. Abstract: There are approximately (2–4)·10 11 stars in the Galaxy. Many of these stars produce stellar flares, that is, they are active stars. It is known that our Sun accelerates charged particles during powerful solar flares. If solar and stellar flares are compared, one can find many common features in these phenomena, and it is generally assumed that the underlying mechanism in solar and stellar flares is the same. To explain the experimental data on cosmic rays obtained recently using balloons and space experiments, the existence of cosmic ray sources near the solar system is required. In the present article, we discuss briefly some cosmic ray experimental data that can be explained if sources of cosmic rays exist near the solar system. We consider active dwarf stars as cosmic ray sources (in addition to supernova remnants). These stars constitute the main stellar population in the Galaxy and generate powerful stellar flares, which are much more powerful than solar ones (up to 10 7 times). This suggestion enables to understand many features observed in cosmic rays over the past 20 years. In particular, the explanation of the positron excess is given in the frame of the known mechanisms without attracting dark matter.